A Bibliometric Analysis of the Islamic Capital Market: Future Research Trends (Jurnal Cendekia Keuangan, 2026)
Introduction/ Main Objectives: This study aims to identify the trends in the growth of scientific publications that focus on authors, affiliations, journal names, and countries that make significant contributions to the literature on Islamic capital markets. This research is grounded in the importance of the role of Islamic capital markets in supporting the growth of the Islamic economy, as well as the necessity for adaptation to technological innovations and the dynamics of investor behavior. Novelty: This study lies in the utilization of recent literature and bibliometric analysis, thereby providing insights into the future direction of research topics. Research Methods: This research employs a bibliometric approach and a systematic literature review to examine publication trends and the research trajectory of Islamic capital markets over the past five years. Finding/Results: The findings indicate the evolution and trends within the literature on Islamic capital markets, as well as how this field continues to develop with the integration of technology, sustainability, and the complexities of the global market. Conclusion: The bibliometric analysis reveals that research in Islamic capital markets remains predominantly descriptive and conceptual, highlighting the need for the development of empirical research with an integrative theoretical model that combines Sharia principles, ESG, digital technology, and the psychological aspects of investors. Research limitation/implications: The limitations of this study are confined to literature published in the last five years and the use of bibliometric analysis; therefore, future research is recommended to utilize a longer data span and a mixed-method approach for more comprehensive results.